Water use efficiency in four irrigation regimes in bulb onion production in the Alto Chicamocha Irrigation District (2020)
The bulb onion is one of the most important agricultural products in Colombia. The productive conditions of the Riego del Alto Chicamocha (Boyaca) district are a regional and national benchmark for this market. The objective of this research was to evaluate four irrigation regimes in terms of production and irrigation water efficiency in bulb onion crops. This trial was in the municipality of Nobsa, village of Dicho (Boyaca). A completely randomized design with four treatments was used: irrigation regime with 150% evapotranspiration (Evt); moisture-based irrigation regime, detected with soil moisture sensors; irrigation regime with 100% Evt; irrigation regime with 60% Evt, along with four repetitions. Starting three weeks after transplant and for 11 weeks (77 days), the polar diameter (cm), equatorial diameter (cm), root length (cm), leaf length (cm), SPAD units, stomatal conductance and irrigation water use efficiency were determined. The irrigation regime with 100% Evt had the best performance in terms of the polar and equatorial diameters and the root and leaf lengths, which were reflected in the fresh weight at harvest. The irrigation regime with soil moisture values obtained from remote sensors, with lower amounts of applied water, had better values for the transformation of water to fresh mass, with 13.64 kg mm-1.